Stature estimation in a contemporary Japanese population based on clavicular measurements using multidetector computed tomography - Torimitsu, Suguru; Makino, Yohsuke; Saitoh, Hisako; Sakuma, Ayaka; Ishii, Namiko; Yajima, Daisuke; Inokuchi, Go; Motomura, Ayumi; Chiba, Fumiko; Yamaguchi, Rutsuko; Hashimoto, Mari; Hoshioka, Yumi; et al. (Forensic Science International, 2017)
[Display omitted] •We assessed correlation between stature and 1 clavicular measurements.•Regression analyses showed significant correlations.•We derived regression formulae for estimating stature in a Japanese population.•Clavicular measurements may be useful tools for stature estimation. The aims of this study was to assess the correlation between stature and clavicular measurements in a contemporary Japanese population using three-dimensional (3D) computed tomographic (CT) images, and to establish regression equations for predicting stature. A total of 249 cadavers (131 males, 118 females) underwent postmortem CT scanning and subsequent forensic autopsy between October 2011 and May 2016 in our department. Four clavicular variables (linear distances between the superior margins of the left and right sternal facets to the anterior points of the left and right acromial ends and between the superior margins of the left and right sternal facets to the left and right conoid tubercles) were measured using 3D CT reconstructed images that extracted only bone data. The correlations between stature and each of the clavicular measurements were assessed with Pearson product–moment correlation coefficients. These clavicular measurements correlated significantly with stature in both sexes. The lowest standard error of estimation value in all, male, and female subjects was 3.62cm (r2=0.836), 3.55cm (r2=0.566), and 3.43cm (r2=0.663), respectively. In conclusion, clavicular measurements obtained from 3D CT images may be useful for stature estimation of Japanese individuals, particularly in cases where better predictors, such as long bones, are not available.